The manipulator behind “Scissors”: γ -secretase and its modulators in Alzheimer’s disease - Ning, Gao; Fan, Xing; Juan, Du; wenxue, Zhao; Sijia, Wang; Meinei, Chen; Xiaolong, Dong; Yiming, Qi (Frontiers in Aging Neuroscience, 2025)
The intramembrane aspartic protease, γ-secretase, is a heterotetrameric protein complex composed of four integral membrane proteins: presenilin (PSEN), nicastrin (NCT), Anterior pharynx defective-1 (APH-1), and presenilin enhancer 2 (PEN-2). These components are sequentially assembled into a functional complex. γ-secretase is ubiquitously expressed in all cells and tissues and exhibits enzymatic activity akin to “molecular scissors” by cleaving various type I transmembrane proteins. The primary substrates of this complex include amyloid precursor protein (APP) and Notch. The role of APP in the pathogenesis of Alzheimer’s disease (AD) has been extensively investigated. Although γ-secretase inhibitors (GSIs) have been evaluated for their therapeutic potential in AD, their clinical application is limited due to significant toxic side effects. Recently, γ-secretase modulators (GSMs) have emerged as promising alternatives, offering new opportunities for the treatment of AD, especially the inherent γ-secretase modulatory proteins (GSMPs) within cells. Research on GSMPs has ushered in a new era for mitigating the side effects of AD drugs. In this review, we systematically summarize recent advancements in the study of γ-secretase in relation to AD and provide an overview of GSMs and GSMPs, thereby offering potential insights for the development of therapeutic strategies for AD.